A Hypothesis Regarding Neurosecretory Inhibition of Stress Mediators by Colchicine in Preventing Stress-Induced Familial Mediterranean Fever Attacks - Korkmaz, Cengiz; Cansu, Döndü Üsküdar; Cansu, Güven Barıs (Frontiers in Immunology, 2022)
Familial Mediterranean fever (FMF) is a monogenic autoinflammatory disease characterized by recurrent episodes of fever and serositis. Colchicine (Col) has a crucial role in the prevention of amyloidosis and FMF attacks. The effect of Col on innate immune cells is based on the inhibition of the microtubule system. The microtubule system is also very important for neurosecretory functions. The inhibitory effect of Col on neurosecretory functions is an overlooked issue. Considering that the neuroimmune cross-talk process plays a role in the development of inflammatory diseases, the effect of Col on the neuronal system becomes important. FMF attacks are related to emotional stress. Therefore, the effect of Col on stress mediators is taken into consideration. In this hypothetical review, we discuss the possible effects of Col on the central nervous systems (CNS) and peripheral nervous systems (PNS) in light of mostly experimental study findings using animal models. Studies to be carried out on this subject will shed light on the pathogenesis of FMF attacks and the other possible mechanisms of action of Col apart from the anti-inflammatory features.